ANTICANCER STUDIES OF ZERUMBONE-LOADED CHITOSAN-OLEIC ACID NANOPARTICLES AGAINST T47D BREAST CANCER CELLS - WIKANTYASNING, ERINDYAH R; MAZIDAH, ZULFA; DA’I, MUHAMMAD; KUSUMAWATI, IKA TD; SUPRAPTO, SUPRAPTO (International Journal of Applied Pharmaceutics, 2024)
Objective: The phytochemical compound zerumbone is derived from the rhizome of Zingiber zerumbet (L.) Smith. Nanotechnology-based drug delivery system employing chitosan-oleic acid nanoparticles to transport zerumbone. This study aimed to examine the cytotoxic activity of zerumbone nanoparticles against T47D breast cancer cells. Methods: Using the ionic gelation method, zerumbone-loaded chitosan-oleic acid nanoparticles were synthesized and characterized for particle size, zeta potential, morphology, and encapsulation efficiency. Utilizing the MTT assay, flow cytometry, and confocal microscopy, the cytotoxic activity of nanoparticles was evaluated. Results: The characterization of zerumbone nanoparticles resulted in a particle size of 116±12.04 nm, polydispersity index of 0.74±0.07 μm, and zeta potential of (+34.4) mV. HPLC analysis showed an encapsulation efficiency of 92.43±1.73%. The uptake of zerumbone-loaded chitosan-oleic acid nanoparticles into T47D cells induced higher apoptosis than the zerumbone isolate and the control nanoparticles. Conclusion: Zerumbone-loaded chitosan-oleic acid nanoparticles showed anticancer activity against breast cancer cells T47D. Using nanoparticles as a drug delivery system would improve the clinical efficacy of anticancer treatment, which has significant implications for future cancer treatment strategies.